Ugruntowanie autokefalii prawosławia w Polsce współczesnej - Mossakowski, Wiesław (Studia Iuridica Toruniensia, 2012)
<!--[if gte mso 9]> <![endif]--> Author of this paper joints the establish of Orthodox Church’s autocoephalous in Poland with regenerate of Polish State after the 1th World War. The idea of church’s power is composed of: 1) internal elements (in their ecclesiastical hierarchy), 2) external elements (between the church and state’s authority). Special type of autocoephalous had appeared with the fall of Byzantine Empire in 1454. From that time Orthodox Church had been submitted to Sultan of Turkey in the external sphere. The concept of autocoephalic authority gave the independence for Orthodox churches sited in others lands. Early polish Orthodox Church was under Metropolitan of Kijev. However Moscow Cerkev (Church) had obtained the autocoephalous from maternity Church in Constantinople. After the 1th World War, and Bolshevik revolution in Russia liberty contact with Church was unusual. The Superior of Polish Orthodox Hierarchy should ask Patriarch of Moscow and All Russia but it was quite impossible. Especially Superior of Russia’s Church has recognized Polish Orthodox Church as a part of Church of Russia. In the end authority of Polish Orthodoxy asked Patriarch of Constantinople for (blessing) of autocoephalous. For this motion Oecumenical Patriarch of Constantinople had passed the ceremonial proclamation (thomos) promulgated 17 September 1925. Others autocoephalic hierarchies gave acceptances for it. Finally, after many years (1938) President of Poland had been decived decree: “Statute of the state’s Relation to the Polish Authocoephalic Orthodox Church”. But after the 2nd Word War the status of that Church was changing. Polish Authocoephalic Orthodox Church was forced into concessions of recognize power of Patriarch Church in Moscow, and the autocoephalous of 1925 was non canonical and illegal. In the end Patriarch of Moscow and All Russia grated an authocoephalous in 22 June 1948. After the fall of communism Polish Parliament gave “Act of the State’s Relation to the Polish Authocoephalic Orthodox Church in Poland” in 1991. In opinion of this paper’s author there are important the analyses of two problems concerned in public law’s aspects of autocoephalous: legal consequences of Orthodoxy’s power in Church, and consequence of Orthodoxy’s to the state’s public power. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->